Correlation Between Six-Minute Walk Test and Treadmill Exercise in Post-Coronary Artery Bypass Phase II Rehabilitation Patients: A Cross-Sectional Study - Tresia Fransiska Ulianna Tambunan; Audrey Witari; Helisa Rachel Patricie Sianipar (Jurnal Kardiologi Indonesia, 2026)
Background: Coronary Artery Bypass Grafting (CABG) improves survival in advanced Coronary Artery Disease (CAD) but is often associated with reduced functional capacity during recovery. Phase II cardiac rehabilitation improves physical performance, yet accessible and reliable tools are needed to monitor progress. Treadmill Cardiopulmonary Exercise Testing (CPET) is the gold standard for assessing aerobic capacity, but it is resource-intensive and not widely available in many settings. The Six-Minute Walk Test (6MWT) is a simple alternative, but its validity compared with treadmill testing in Indonesian post-CABG patientsremains underexplored Methods: This cross-sectional study was conducted at the National General Hospital Dr. Cipto Mangunkusumo in Jakarta between May 2023 and October 2024. Post-CABG patients who completed an eight-week Phase II cardiac rehabilitation program, were clinically stable, and able to perform both assessments were included. Functional capacity was determined by estimated VO2Max from the 6MWT and directly measured VO2Max from a symptom-limited treadmill test using the Modified Bruce protocol. Descriptive statistics summarized baseline characteristics. Spearman correlation coefficient was used to evaluate the relationshipbetween the two tests, with statistical significance set at p<0.05. Results: Fifteen post-CABG patients completed the study. Most were male (73.3%) with a mean age of 59 years. Overweight status was common (46.7%), with hypertension (80.0%), dyslipidemia (66.7%), and diabetes mellitus (53.3%) as frequent comorbidities. Mean 6MWTdistance increased from 307.8 ± 85.7 m pre-rehabilitation to 498.5 ± 140.7 m post-rehabilitation. The estimated VO2Max from the 6MWT followed a normal distribution and is reported as a mean of 18.9 mL/kg/min (SD = 4.2). In contrast, the treadmill-measured VO2Max was nonnormally distributed and is therefore reported as a median of 21.4 mL/kg/min. A significant moderate positive correlation was found between 6MWT and treadmill VO2Max (r = 0.689, p = 0.005). Conclusion: The 6MWT demonstrated a strong, significant correlation with treadmill-based VO2Max, supporting its use as a practical and cost-effective alternative for functional capacity assessment in post-CABG Phase II rehabilitation. Routine integration of the 6MWT may facilitate individualized exercise prescription and enhance patient monitoring, particularly in resource-limited settings.